2019
DOI: 10.1097/md.0000000000017865
|View full text |Cite
|
Sign up to set email alerts
|

Compressive peroneal neuropathy by an intraneural ganglion cyst combined with L5 radiculopathy

Abstract: Rationale: Most cases of foot drop are known to result from lower motor neuron pathologies, particularly lumbar radiculopathy and peripheral neuropathy, including common peroneal neuropathy. To improve the prognosis of foot drop, it is important to quickly and accurately diagnose the etiology and provide appropriate treatment. Patient concerns: A 65-year-old female patient with a history of L4-5 intervertebral disc herniation presented with right foot d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Table 2 summarizes case reports of the cyst around knee that were previously reported according to the classification. [ 10 , 11 , 14 , 16 , 19 23 ] To our knowledge, our case is the first report of compressive peroneal neuropathy caused by extraneural type of ganglion cyst in the supracondylar area of femur. Ganglion cyst compressions of the peroneal nerve can be classified as intraneural or extraneural lesions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Table 2 summarizes case reports of the cyst around knee that were previously reported according to the classification. [ 10 , 11 , 14 , 16 , 19 23 ] To our knowledge, our case is the first report of compressive peroneal neuropathy caused by extraneural type of ganglion cyst in the supracondylar area of femur. Ganglion cyst compressions of the peroneal nerve can be classified as intraneural or extraneural lesions.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, a few studies have reported the development of peroneal neuropathy caused by intraneural-type cysts formed in the popliteal fossa. [ 16 , 17 ] To the best of our knowledge, no reports have described a case of common peroneal neuropathy caused by an extraneural ganglion cyst located at the proximal site of popliteal fossa.…”
Section: Introductionmentioning
confidence: 99%
“…L5 is the most frequently affected nerve root in LCSS. Peroneal and tibial nerves receive a significant contribution of fibers from this root and thus constitute a suitable target for NCS [ 18 ]. Since LCSS provokes a focal injury on the nerve, Wallerian degeneration can occur distally, which seems to contribute to the lowered amplitude of CMAPs of peroneal and tibial nerves [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPN compression secondary to a cystic tibiofibular joint was reported in various cases. 41,[43][44][45] Two such cases described CPN compression due to intraneural ganglion and synovial cysts. 41,45 Complete return of motor function was accomplished via cyst aspiration in one case, while the other was treated with prompt surgical cyst removal and nerve decompression.…”
Section: Case Reports Common Peroneal Nervementioning
confidence: 99%
“…41,45 Complete return of motor function was accomplished via cyst aspiration in one case, while the other was treated with prompt surgical cyst removal and nerve decompression. 43,44 Two other reports of cystic etiologies included an extraneural popliteal cyst and two cases of children with extraneural tibiofibular joint synovial cysts, all of which were treated with surgical cyst removal and CPN decompression. 45,46 CPN compression due to bony growths were also commonly reported in multiple case reports.…”
Section: Case Reports Common Peroneal Nervementioning
confidence: 99%